2022
DOI: 10.1186/s12889-022-13399-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on chronic non-communicable disease in disaster settings

Abstract: Background Non-communicable diseases (NCDs) constitute the leading cause of mortality globally. Low and middle-income countries (LMICs) not only experience the largest burden of humanitarian emergencies but are also disproportionately affected by NCDs, yet primary focus on the topic is lagging. We conducted a systematic review on the effect of humanitarian disasters on NCDs in LMICs assessing epidemiology, interventions, and treatment. Methods A sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 111 publications
0
16
0
1
Order By: Relevance
“…Our study also revealed that more than half of the refugee health research grants focused on mental health as their primary research without equal emphasis on other aspects of health among refugees, including chronic and infectious diseases . US-resettled refugees have a high burden of chronic noncommunicable disease and face major barriers to managing these conditions compared with native-born populations . Our study underscores the need to expand NIH-funded refugee health research beyond focusing only on mental health, which comprised the main topic area of almost half of all NIH-supported refugee health research.…”
Section: Discussionmentioning
confidence: 74%
“…Our study also revealed that more than half of the refugee health research grants focused on mental health as their primary research without equal emphasis on other aspects of health among refugees, including chronic and infectious diseases . US-resettled refugees have a high burden of chronic noncommunicable disease and face major barriers to managing these conditions compared with native-born populations . Our study underscores the need to expand NIH-funded refugee health research beyond focusing only on mental health, which comprised the main topic area of almost half of all NIH-supported refugee health research.…”
Section: Discussionmentioning
confidence: 74%
“…Em relação ao diagnóstico médico prévio para as condições investigadas, as prevalências foram relativamente superiores ao reportado na RMBH e em MG. Essa maior prevalência pode estar relacionada ao desastre ocorrido no município, considerando que alguns estudos demonstram maior carga de doenças após um grande evento 3,4,6,7,[37][38][39] , mas também se deve considerar a cobertura universal da ESF no município 19 , o que pode aumentar o acesso aos serviços e ao diagnóstico médico 40,41 , sobretudo se a população passou a buscar mais esse serviço após o desastre.…”
Section: Discussionunclassified
“…Regarding previous medical diagnoses for the conditions investigated, the prevalence was relatively higher than that reported in the MRBH and Minas Gerais. This higher prevalence may be related to the disaster, considering that some studies show a greater burden of disease after a major event 3,4,6,7,[37][38][39] , but one should also consider the universal coverage of the FHS in the municipality 19 , which can increase access to services and medical diagnosis 40,41 , especially if the population started to seek this service more after the event.…”
Section: Discussionmentioning
confidence: 99%